1999
DOI: 10.1007/s001250051199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin converting enzyme inhibitor or beta blocker on glomerular structural changes in young microalbuminuric patients with Type I (insulin-dependent) diabetes mellitus

Abstract: Long-term treatment with angiotensin converting enzyme inhibitors (ACEI) has a beneficial effect on the progression of microalbuminuria in patients with Type I (insulin-dependent) diabetes mellitus [1,2]. In addition, some clinical studies but not all [3±5] have suggested a superior effect of ACE-inhibitors over beta-blockers on the progressive decline in glomerular filtration rate (GFR) in Type I diabetic patients with nephropathy.Microalbuminuria predicts overt diabetic renal disease [6]. Still around 30 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
3
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 20 publications
4
71
3
2
Order By: Relevance
“…Indeed, there was no change over this time interval in any structural parameter in the enalapril, nifedipine or placebo groups. Another study compared renal structure before and after 38 months of treatment with enalapril or metoprolol in 13 type 1 diabetic patients with microalbuminuria [62], reporting no change over time in either group. In 19 type 2 diabetic patients, 2 years of treatment with perindopril prevented the progression of interstitial fibrosis compared with controls [63], without affecting glomerular structure.…”
Section: Pathways Of Repair: Reversal Of Diabetic Renal Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there was no change over this time interval in any structural parameter in the enalapril, nifedipine or placebo groups. Another study compared renal structure before and after 38 months of treatment with enalapril or metoprolol in 13 type 1 diabetic patients with microalbuminuria [62], reporting no change over time in either group. In 19 type 2 diabetic patients, 2 years of treatment with perindopril prevented the progression of interstitial fibrosis compared with controls [63], without affecting glomerular structure.…”
Section: Pathways Of Repair: Reversal Of Diabetic Renal Injurymentioning
confidence: 99%
“…Thus, as clearly demonstrated by the studies performed to date [61][62][63], clinical trials using renal structure as an endpoint, especially in the early stages of DN, require large numbers and, most importantly, a long follow-up duration (likely 7-10 years). This would require the cooperation of industries and national funding agencies, along with strong commitment from the investigators and patients.…”
Section: Pathways Of Repair: Reversal Of Diabetic Renal Injurymentioning
confidence: 99%
“…In the study on type 1 diabetic patients with microalbuminuria, treatment with enalapril, perindopril, or metoprolol resulted in a decrease in glomerular basement membrane thickness after 3-4 years of follow-up (Nankervis et al, 1998) (Rudberg et al, 1999). Other studies have suggested that glomerular volumes may be reduced by RAS inhibition, however the contribution of changes in blood pressure is unclear (Perrin et al, 2008).…”
Section: Clinical Studies Of Ckd Regressionmentioning
confidence: 99%
“…26 Thirteen patients with Type 1 diabetes mellitus and microalbuminuria were treated with either enalapril or metoprolol. Renal biopsies were taken before and after 38 months of treatment.…”
Section: Ace-i Intervention: Effects On Gfr and Glomerulopathymentioning
confidence: 99%
“…44 In a number of clinical trials encompassing microalbuminuric Type 1 diabetic patients, antihypertensive treatment in particular with ACE inhibitors (ACE-I), has been shown to reduce albuminuria. 45,46 Importantly, data suggesting positive effects on harder endpoints such as GFR 25 and glomerulopathy 26 are now emerging. At present, the consensus calls for antihypertensive treatment in most patients with microalbuminuria, regardless of BP.…”
Section: Introductionmentioning
confidence: 99%